Exercise and cognitive functions in Parkinson's disease: Gender differences and disease severity - Claudia Teixeira-Arroyo; Natália Madalena Rinaldi; Rosangela Alice Batistela; Fabio Augusto Barbieri; Rodrigo Vitório; Lilian Teresa Bucken Gobbi (Universidade Estadual Paulista (UNESP), 2014)
This study investigated the effect of a multimodal exercise program on executive functions and memory in people with Parkinson's disease, taking into account disease severity and gender. Twenty-three patients with Parkinson's disease (PD) were evaluated before and after a 6-month exercise program to improve executive functions and memory. We observed the effects of the intervention on executive functions (ability to abstract: p = .01), immediate memory (p= .04) and declarative episodic memory (p < .001). Women showed higher scores on declarative episodic memory (p = .03) than men, however there was no interaction between gender and the intervention. Regardless of sex and disease severity, these preliminary results indicate that the multimodal exercise seems to be effective in improving cognitive functions in patients with PD, suggesting that this program can be indicated as a preventive strategy to mitigate progressive cognitive deficits in the later stages of the disease.